2022
DOI: 10.1021/jacs.2c01594
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Diagnostics and Synthetic Design of Platinum Group Metal-Free Electrocatalysts for the Oxygen Reduction Reaction Using Reactivity Maps and Site Utilization Descriptors

Abstract: The experimental development of catalytically ever-more active platinum group metal (PGM)-free materials for the oxygen reduction reaction (ORR) at fuel cell cathodes has been until recently a rather empirical iteration of synthesis and testing. Here, we present how kinetic reactivity maps based on kinetic descriptors of PGM-free single-metal-site ORR electrocatalysts can help to better understand the origin of catalytic reactivity and help to derive rational synthetic guidelines toward improved catalysts. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…[35] This gives a lower bound active site density compared to CO cryo-chemisorption, which can probe electrochemically inaccessible sites and can also derive another utilisation factor. [28,64] A high initial SDnitrite of 2.54×10 19 sites gFeNC -1 is observed for TAP 900@Fe (Figure 6c). Kumar et al recently found in situ nitrite stripping also probes iron oxides that formed in situ as a result of degradation of FeNx sites.…”
Section: Resultsmentioning
confidence: 96%
“…[35] This gives a lower bound active site density compared to CO cryo-chemisorption, which can probe electrochemically inaccessible sites and can also derive another utilisation factor. [28,64] A high initial SDnitrite of 2.54×10 19 sites gFeNC -1 is observed for TAP 900@Fe (Figure 6c). Kumar et al recently found in situ nitrite stripping also probes iron oxides that formed in situ as a result of degradation of FeNx sites.…”
Section: Resultsmentioning
confidence: 96%
“…Among the studied FeN 4 −Ls, FeN 4 − NH 2 with the highest intrinsic U onset exhibits the optimal ORR performance. Furthermore, it is found that axial ligand/metal coordination affects the electronic structure of Fe sites, especially the d z 2…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electrocatalysis of oxygen reduction reaction (ORR) is essential for fuel cell technology, which is promising for mitigating the ever-growing energy demands. Although the fuel cell technology has come a long way, its critical dependency on platinum-based catalysts makes such devices cost-prohibitive for large-scale commercialization. The single atom catalysts (SACs) with tunable electronic structures and 100% metal atom utilization have received considerable interest as a potential economical alternative to the traditional platinum-based electrocatalysts. Among the investigated metal SACs, the Fe–N–C catalyst has attracted extensive attention and has been massively synthesized to catalyze the oxygen reduction reaction, benefiting from its high activity that rivals that of the state-or-the-art Pt-based electrocatalysts. , The Fe–N–C catalyst can efficiently facilitate 4-electron transfer for H 2 O formation, yet the intrinsic catalytic site of Fe–N–C underlying its outstanding electrocatalytic activity is still ambiguous. Therefore, identifying the actual structure of Fe–N–C catalyst and increasing its activity are of realistic significance for boosting the catalytic performance of SACs.…”
Section: Introductionmentioning
confidence: 99%
“…5). 27,31,32,39,55,60,61,63 Notably, the TOF of Meso-Fe-N/C_2.0 under acidic conditions exceeds the reported TOFs of Fe-N/C catalysts evaluated by the cryo-CO adsorption method. Notably, its value is even 1.6 times greater than that of the PANI-CM catalyst, 32,59 which is one of the highperforming Fe-N/C catalysts (Table S8, ESI †).…”
Section: Resultsmentioning
confidence: 88%
“…Synthetic advances in M-N/C catalysts that increase the density of accessible M-N x sites have enabled remarkable enhancement of their ORR activity; [32][33][34][35][36][37][38][39][40][41][42][43][44][45] effective suppression of undesirable H 2 O 2 formation has boosted long-term durability; [46][47][48][49] molecular-level synthetic control and precise speciation of M-N x sites have helped to identify active sites; [50][51][52][53][54] the exploration of non-d-block compositions has uncovered new p-and s-block-element-based M-N/C catalysts; [55][56][57][58] and the standardization of active site quantification and turnover frequency (TOF) calculations has made the comparison of catalytic activity data from multiple laboratories on fair ground. [59][60][61][62][63][64] One of the outstanding issues in heterogeneous M-N/C catalysts is the realization of a structural analog of the enzymatic ORR catalyst cytochrome c oxidase (CcO). CcO contains a bimetallic center of Fe and Cu and catalyzes the ORR with excellent efficiency under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%